Hierarchization of Educational Elements based on Morganov-Heredia Matrices using Hypergraphs - Miguel Olvera-Aldana; Guillermo Silva Peña; Alejandra Gabriela Guerrero Arreola; Mario Humberto Ramírez Díaz (Migration Letters, 2023)
For educational institutions in general and teachers in particular, it is important to be able to prioritize thematic contents, objectives and competencies, among others, for their study plans and programs. To carry out this hierarchy, analysis techniques are responsible for obtaining an optimal sequence from the vague idea that a person (in this case managers or teachers) initially has about the sequence relationship between the elements to be studied. One of these techniques is the hypergraph (which is a generalization of a graph), and can relate any number of vertices, instead of only a maximum of two as in the particular case, to determine a logical sequence of the elements to be hierarchize based on the criteria managed by a person or group and, by virtue of mathematical formalism, allows its application to be carried out by a computer. This work describes the Hypergraph technique used to provide a solution to one of the sequencing techniques called Morganov-Heredia matrices, which is based on the relationship of rows and columns to prioritize the elements, using specific competencies as a particular case.